Abstracts of the SA Heart Congress 2010 - Abbasi, Haroon; Libhaber, Elena; Norton, Gavin; Woodiwiss, Angela; Sliwa, Karen; Essop, Rafique (SA Heart Journal, 2017)
Introduction: The pathophysiology of left ventricular (LV) remodelling in patients with hypertension (HT) is unclear. Aim: To evaluate the impact of four different types of geometric adaptations to hypertension on left ventricular ejection fraction (LVEF). Methods: A prospective single-centre study of 175 Black African patients (55% female, age = 53.1 ± 10.1 years) with moderate-to-severe HT was performed. HT was defined as systolic or diastolic daytime ambulatory BP (ABPM) >140mmHg or 95mmHg respectively. Echocardiography was performed using a HP 1 500 machine connected to 2.5 MHZ transducer. LV dimensions (LVEDD, LVESD, LVEF) were measured using standard American Society of Echocardiography definitions. Comparisons between the four geometric patterns were analysed using the Kruskal-Wallis test. Conclusion: Patients with eccentric LVH have the lowest systolic performance as measured by LVEF. These results suggest that patients with eccentric LVH need more aggressive therapy for heart failure.